Pigment with wire drawing effect and preparation method and application thereof

By using sodium polyacrylate/polyethylene oxide/cellulose nanocrystalline water-in-water emulsion and other modified ingredients, the problem of poor stability of existing brushed pigments at high temperatures is solved, and the long-term stability and efficient use of pigments under different temperature conditions are achieved.

CN118909478BActive Publication Date: 2025-04-01HEYUAN CITY WINGART ENTERPRISES CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411138248.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-04-01
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

The existing brushed pigments have poor storage stability, especially when decomposition reactions are prone to occur under high temperature conditions, resulting in reduced performance and shortened service life.

Method used

Sodium polyacrylate/polyethylene oxide/cellulose nanocrystalline water-in-water emulsion is used as the main components, and a high stability brushed pigment is formed by adding components such as sodium polyacrylate modified shell powder and Sanzan glue.

Benefits of technology

It improves the low temperature and high temperature resistance of pigments, extends the shelf life of storage, and ensures that the pigments maintain stability and use effect under different temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118909478B_ABST
    Figure CN118909478B_ABST
Patent Text Reader

Abstract

The present invention relates to a pigment with a wire drawing effect and a preparation method and application thereof, and belongs to the technical field of pigments. A pigment with a wire drawing effect comprises the following components by mass: 15-20 parts of sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion, 5-10 parts of sodium polyacrylate modified shell powder, 1-5 parts of tri-zan gum, 5-10 parts of pearl powder, 0.2-0.5 parts of defoamer, 0.1-0.3 parts of preservative, 0.3-1 parts of pH regulator and 60-80 parts of water; the mass concentration of cellulose nanocrystals in the emulsion is 0.15-0.25wt%. The pigment of the present invention has a wire drawing effect, and the wire drawing length can reach 25-35cm, and the pigment can be stably placed at a low temperature of 18°C ​​and a high temperature of 55°C for 3 months, and will not be hydrolyzed and invalidated at room temperature for 12 months, and has good storage stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pigments, and in particular to a pigment with a wire drawing effect and a preparation method and application thereof. Background Art

[0002] The selection of children's painting pigments pays more attention to safety, non-toxicity and whether it is easy to clean. However, the pigment is difficult to operate for children because they are not skilled in the early stage of painting, it is difficult to draw a straight line, and it is easy to get the pigment all over their bodies. Chinese patent CN1322071C discloses a drawing pigment and a production method thereof, which does not need to be connected to the surface of the painting carrier, only needs to contact the starting point and the end point to complete the drawing of a straight line, so that beginners or children can easily complete complex painting connections. However, the main component thereof is polyethylene oxide (PEO), which is easily attacked by oxygen and degraded due to a large amount of ether bonds (COC) contained in its molecular chain. At high temperatures, PEO is prone to changes in molecular structure and decomposition reactions, which impair its physical properties and durability, accelerate the reaction with oxygen and moisture in the environment, and cause oxidation and deterioration. Therefore, the common drawing pigment containing PEO has poor storage stability, and is hydrolyzed and ineffective at room temperature for 3-6 months, and is ineffective faster at high temperatures. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a pigment with a drawing effect and a preparation method and application thereof, which has the advantages of good low-temperature resistance and high-temperature resistance and a long storage shelf life.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] In the first aspect, the present invention provides a pigment with a brushed effect, which comprises the following components, measured by mass: 15 to 20 parts of sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion, 5 to 10 parts of sodium polyacrylate modified shell powder, 1 to 5 parts of tri-zan gum, 5 to 10 parts of pearl powder, 0.2 to 0.5 parts of defoaming agent, 0.1 to 0.3 parts of preservative, 0.3 to 1 parts of pH adjuster and 60-80 parts of water; wherein the mass concentration of polyethylene oxide in the emulsion is 1.5 to 1.8wt%, the mass concentration of sodium polyacrylate is 25 to 30wt%, and the mass concentration of the cellulose nanocrystal is 0.15 to 0.25wt%.

[0006] The functions of the components in the above pigments are as follows:

[0007] Sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion is a water-in-water emulsion of a two-phase system, mainly formed by a mixture of two thermodynamically immiscible hydrophilic polymer aqueous solutions of sodium polyacrylate (PAA-Na) and polyethylene oxide (PEO). This emulsion has extremely low interfacial tension and a thick interfacial layer, so it is difficult to stabilize it with traditional surfactants. However, based on the Pickering emulsion stabilization mechanism, cellulose nanocrystal emulsion is added as a solid particle, and its irreversible adsorption at the water-water interface can improve the stability of the W / W emulsion.

[0008] Compared with common water-in-oil emulsions and oil-in-water emulsions, water-in-water emulsions have higher stability and are not prone to phase separation or demulsification. Moreover, their emulsion systems can protect polyethylene oxide from the effects of high temperatures, thereby improving the high temperature resistance and storage period of the pigment. In addition, their emulsion systems can also serve as carriers for pigment particles in pearlescent powder to improve their dispersibility in water.

[0009] Wherein, the mass concentration of cellulose nanocrystals in the emulsion is 0.15-0.25wt%. If the amount of cellulose nanocrystal dispersion added is less than 0.15wt%, because the salt solution is added, there are still positive ions in the system, but the surface of the cellulose nanocrystals has a high surface negative charge, so the two will combine, resulting in the agglomeration of the emulsion droplets, and the stability of the emulsion will be significantly reduced. Within the range of 0.15-0.25wt%, the emulsion will not phase separate and can maintain good stability. If the amount of cellulose nanocrystal dispersion added is higher than 0.25wt%, obvious cellulose nanocrystal agglomerates will appear in the emulsion, and the stability of the emulsion will also be reduced.

[0010] Sodium polyacrylate modified shell powder is used as a stabilizer and dispersant. Shell powder is wrapped by the three-dimensional cross-linked network of sodium polyacrylate, which increases the water conductivity of shell powder, improves wettability and hydrophilicity, and can be used as an additive to improve the dispersibility of solid particles in liquid media, thereby avoiding the aggregation of color ions in pearlescent powder. At the same time, shell powder, as a skeleton, can provide strength and toughness for the drawing of pigments.

[0011] As a suspending agent, Sanzan gum can prevent the sedimentation and aggregation of pigment particles, ensuring that the pigment remains stable during storage and use. Sanzan gum has good thickening, emulsification, weak gel and synergistic properties under high temperature, high pressure, high salt and high oil conditions, further strengthening the structure of sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion and improving its stability.

[0012] Preferably, the method for preparing the sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion comprises the following steps:

[0013] (1) mixing a polyethylene oxide dispersion and a sodium polyacrylate dispersion under stirring to obtain a transparent and clear polyethylene oxide and sodium polyacrylate water-in-water emulsion;

[0014] (2) adding the cellulose nanocrystal dispersion to the polyethylene oxide and sodium polyacrylate water-in-water emulsion, stirring evenly, and then adding the salt solution, stirring evenly to obtain a sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion.

[0015] Preferably, the method for preparing the cellulose nanocrystal dispersion comprises the following steps:

[0016] The microcrystalline cellulose powder is added to a sulfuric acid solution for hydrolysis reaction, and then a large amount of water is added to terminate the reaction, and then centrifuged and washed with water until the pH of the system is 6 to 7, and the turbid supernatant is taken to obtain the cellulose nanocrystal dispersion. Because the sulfate groups are introduced on the cellulose surface, the surface of the cellulose nanocrystal has a high surface negative charge, the electrostatic repulsion between the particles is strong, and the water dispersion stability is good.

[0017] Preferably, the mass concentration of the sulfuric acid solution is 50-60wt%, more preferably 55wt%. The temperature of the hydrolysis reaction is 40-60°C, and the time is 1-2h. The mass ratio of microcrystalline cellulose powder to sulfuric acid solution is 1:(4-10).

[0018] Preferably, the salt solution is a sodium chloride solution with a molar concentration of 30 to 100 mmol / L. The cellulose nanocrystal dispersion will form a gel in the salt solution, and the concentration of the salt solution will affect the strength and formation rate of the gel. If the molar concentration of the salt solution is lower than 30 mM, phase separation will occur, that is, it is difficult to form a stable gel structure; if the molar concentration of the salt solution is higher than 100 mM, the cellulose nanocrystal particles will quickly aggregate, thereby affecting the interfacial adsorption of the particles and causing the emulsion droplets to aggregate. Therefore, the molar concentration of the salt solution is within the range of 30 to 100 mmol / L, which can enable the water-in-water emulsion to obtain a relatively stable gel structure.

[0019] Preferably, the method for preparing the sodium polyacrylate modified shell powder comprises the following steps:

[0020] The shell powder, sodium acrylate and initiator are mixed in water and subjected to polymerization reaction to obtain the sodium polyacrylate modified shell powder; wherein the mass ratio of the sodium acrylate to the initiator is 1:0.015-0.020, and the mass ratio of the sodium acrylate to the shell powder is 1:(4-6); wherein sodium polyacrylate (PAA-Na) is used as a polymer to modify the shell powder, thereby improving its chemical compatibility and hydrophilicity.

[0021] Preferably, the initiator is potassium persulfate.

[0022] Preferably, the polymerization reaction temperature is 70-80° C. and the time is 1-3 hours.

[0023] Preferably, the pH adjuster is aminomethyl propanol.

[0024] Preferably, the defoaming agent is ethylene glycol.

[0025] Preferably, the preservative is isothiazolinone.

[0026] In a second aspect, the present invention provides a method for preparing a pigment having a wire drawing effect, comprising the following steps:

[0027] S1, stirring and mixing water, sodium polyacrylate modified shell powder, pearl powder, Sanzan glue, defoaming agent and preservative to obtain a first mixture;

[0028] S2. Adding sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion and pH regulator into the first mixture and stirring evenly to obtain the pigment with wire drawing effect.

[0029] Preferably, in step S1, the stirring speed is 6000-7000 r / min, and the time is 20-30 min; in step S2, the stirring speed is 2000-3000 r / min, and the time is 10-20 min.

[0030] In a third aspect, the present invention provides a pigment with a brushed effect for use in preparing a children's product.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) In the pigment of the present invention, PEO is wrapped in a water-in-water emulsion, which can significantly improve its stability at low and high temperatures, and the water-in-water emulsion can also serve as a carrier of pigment particles in pearlescent powder to improve its dispersibility in water. In order to improve the strength and toughness of the wire drawing in the pigment, sodium polyacrylate modified shell powder is added, and the shell powder is used as the skeleton of the wire drawing. The shell powder is wrapped by the three-dimensional cross-linked network of sodium polyacrylate, so that the water conductivity of the shell powder is improved, and the wettability and hydrophilicity are improved. Therefore, it can also be used as an additive to improve the dispersibility of solid particles in the liquid medium, thereby avoiding the aggregation of color ions in the pearlescent powder. Sanzan gum is used as a suspending agent to prevent the sedimentation and aggregation of pigment particles, ensuring that the coating remains stable during storage and use. Therefore, the pigment of the present invention has a wire drawing effect, and the wire drawing length can reach 25-35cm. Moreover, the pigment can be stably placed for 3 months at a low temperature of -18°C and a high temperature of 55°C, and will not be hydrolyzed and invalidated at room temperature for 12 months, and has good storage stability.

[0033] (2) The pigment of the present invention does not contain any harmful ingredients such as VOC, and is highly safe. In addition, the pigment is all water-based and easy to clean, and is suitable for use as a children's toy. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a real picture of the pigment after drawing and drying in Example 1;

[0035] Figure 2 This is a product picture of the pigment of the present invention. DETAILED DESCRIPTION

[0036] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0037] The reagent information used in the following examples and comparative example 1 is as follows:

[0038] Sodium polyacrylate: The manufacturer is Guangdong Wengjiang Chemical Reagent Co., Ltd.;

[0039] Polyethylene oxide: The manufacturer is Wuhan Xinyang Ruihe Chemical Technology Co., Ltd.;

[0040] Microcrystalline cellulose: The manufacturer is Shanghai Puzhen Biotechnology Co., Ltd.;

[0041] Shell powder: It comes from river clam shells from Yutan River in Heping County, Heyuan City. After cleaning, it is ground into 300 meshes.

[0042] Sodium acrylate: The manufacturer is Guangdong Yunxing Biotechnology Co., Ltd.

[0043] Potassium persulfate: The manufacturer is Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0044] Aminomethyl propanol: the manufacturer is Sigma-Aldrich (Shanghai) Trading Co., Ltd.

[0045] Ethylene glycol: The manufacturer is Shanghai Aladdin Biochemical Technology Co., Ltd.

[0046] Isothiazolinone: Shanghai MacLean Biochemical Technology Co., Ltd.

[0047] Unless otherwise specified, other materials, reagents, etc. used in the examples can be obtained from commercial sources.

[0048] Example 1

[0049] A pigment with a wire drawing effect comprises the following components, measured by mass: 17 parts of sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion, 6 parts of sodium polyacrylate modified shell powder, 4 parts of trisammonium gum, 8 parts of pearl powder, 0.3 parts of a defoamer, 0.2 parts of a preservative, 0.5 parts of a pH regulator and 67 parts of water; the mass concentration of the polyethylene oxide in the emulsion is 1.7wt%, the mass concentration of the sodium polyacrylate is 28wt%, the mass concentration of the cellulose nanocrystal is 0.20wt%, the pH regulator is aminomethyl propanol, the defoamer is ethylene glycol, and the preservative is isothiazolinone.

[0050] The method for preparing the sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion comprises the following steps:

[0051] (1) mixing a polyethylene oxide dispersion and a sodium polyacrylate dispersion under stirring to obtain a transparent and clear polyethylene oxide and sodium polyacrylate water-in-water emulsion;

[0052] (2) adding a cellulose nanocrystal dispersion to the polyethylene oxide and sodium polyacrylate water-in-water emulsion, stirring evenly, and then adding a salt solution, stirring evenly to obtain a sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion, wherein the salt solution is a sodium chloride solution with a molar concentration of 60 mmol / L.

[0053] The method for preparing the cellulose nanocrystal dispersion comprises the following steps:

[0054] The microcrystalline cellulose powder is added to the sulfuric acid solution for hydrolysis reaction, and then a large amount of water is added to terminate the reaction, and then centrifuged and washed with water until the pH of the system is 6, and the turbid supernatant is taken to obtain the cellulose nanocrystal dispersion. The mass concentration of the sulfuric acid solution is 55wt%. The temperature of the hydrolysis reaction is 50°C and the time is 1.5h. The mass ratio of the microcrystalline cellulose powder to the sulfuric acid solution is 1:7.

[0055] Wherein, the preparation method of the sodium polyacrylate modified shell powder comprises the following steps:

[0056] The shell powder, sodium acrylate and initiator are mixed in water, and a polymerization reaction is carried out at 75° C. for 2 hours to obtain the sodium polyacrylate modified shell powder; wherein the mass ratio of the sodium acrylate to the initiator is 1:0.018, the mass ratio of the sodium acrylate to the shell powder is 1:5, and the initiator is potassium persulfate.

[0057] The method for preparing the pigment with a wire drawing effect comprises the following steps:

[0058] S1, stirring and mixing water, sodium polyacrylate modified shell powder, pearl powder, Sanzan glue, defoaming agent and preservative at a speed of 6500 r / min for 25 min to obtain a first mixture;

[0059] S2. Adding sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion and pH regulator to the first mixture, stirring at a speed of 2500 r / min for 15 min, to obtain the pigment with a wire drawing effect.

[0060] Example 2

[0061] A pigment with a wire drawing effect comprises the following components by weight: 15 parts of sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion, 5 parts of sodium polyacrylate modified shell powder, 1 part of trisammonium gum, 5 parts of pearl powder, 0.2 parts of defoamer, 0.1 parts of preservative, 0.3 parts of pH regulator and 60 parts of water. The mass concentration of polyethylene oxide in the emulsion is 1.5%, the mass concentration of sodium polyacrylate is 20wt%, the mass concentration of cellulose nanocrystal is 0.15wt%, the pH regulator is aminomethyl propanol, the defoamer is ethylene glycol, and the preservative is isothiazolinone.

[0062] The method for preparing the sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion comprises the following steps:

[0063] (1) mixing a polyethylene oxide dispersion and a sodium polyacrylate dispersion under stirring to obtain a transparent and clear polyethylene oxide and sodium polyacrylate water-in-water emulsion;

[0064] (2) adding a cellulose nanocrystal dispersion to the polyethylene oxide and sodium polyacrylate water-in-water emulsion, stirring evenly, and then adding a salt solution, stirring evenly to obtain a sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion, wherein the salt solution is a sodium chloride solution with a molar concentration of 30 mmol / L.

[0065] The method for preparing the cellulose nanocrystal dispersion comprises the following steps:

[0066] The microcrystalline cellulose powder is added to the sulfuric acid solution for hydrolysis reaction, and then a large amount of water is added to terminate the reaction, and then centrifuged and washed with water until the pH of the system is 6, and the turbid supernatant is taken to obtain the cellulose nanocrystal dispersion. The mass concentration of the sulfuric acid solution is 50wt%. The temperature of the hydrolysis reaction is 40°C and the time is 2h. The mass ratio of the microcrystalline cellulose powder to the sulfuric acid solution is 1:4.

[0067] Wherein, the preparation method of the sodium polyacrylate modified shell powder comprises the following steps:

[0068] The shell powder, sodium acrylate and initiator are mixed in water, and a polymerization reaction is carried out at 70° C. for 3 hours to obtain the sodium polyacrylate modified shell powder; wherein the mass ratio of the sodium acrylate to the initiator is 1:0.015, the mass ratio of the sodium acrylate to the shell powder is 1:4, and the initiator is potassium persulfate.

[0069] The method for preparing the pigment with a wire drawing effect comprises the following steps:

[0070] S1, stirring and mixing water, sodium polyacrylate modified shell powder, pearl powder, Sanzan glue, defoaming agent and preservative at a speed of 6000 r / min for 30 min to obtain a first mixture;

[0071] S2. Adding sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion and pH regulator to the first mixture, stirring at a speed of 2000 r / min for 20 minutes, to obtain the pigment with a wire drawing effect.

[0072] Example 3

[0073] A pigment with a brushed effect comprises the following components, measured by mass: 20 parts of sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion, 10 parts of sodium polyacrylate modified shell powder, 5 parts of trisammonium gum, 10 parts of pearlescent powder, 0.5 parts of defoamer, 0.3 parts of preservative, 1 part of pH regulator and 80 parts of water; the mass concentration of polyethylene oxide in the emulsion is 1.8wt%, the mass concentration of sodium polyacrylate is 30wt%, the mass concentration of the cellulose nanocrystal is 0.25wt%, the pH regulator is aminomethyl propanol, the defoamer is ethylene glycol, and the preservative is isothiazolinone.

[0074] The method for preparing the sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion comprises the following steps:

[0075] (1) mixing a polyethylene oxide dispersion and a sodium polyacrylate dispersion under stirring to obtain a transparent and clear polyethylene oxide and sodium polyacrylate water-in-water emulsion;

[0076] (2) adding a cellulose nanocrystal dispersion to the polyethylene oxide and sodium polyacrylate water-in-water emulsion, stirring evenly, and then adding a salt solution, stirring evenly to obtain a sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion, wherein the salt solution is a sodium chloride solution with a molar concentration of 100 mmol / L.

[0077] The method for preparing the cellulose nanocrystal dispersion comprises the following steps:

[0078] The microcrystalline cellulose powder is added to the sulfuric acid solution for hydrolysis reaction, and then a large amount of water is added to terminate the reaction, and then centrifuged and washed with water until the pH value of the system is 7, and the turbid supernatant is taken to obtain the cellulose nanocrystal dispersion. The mass concentration of the sulfuric acid solution is 60wt%. The temperature of the hydrolysis reaction is 60°C and the time is 1h. The mass ratio of the microcrystalline cellulose powder to the sulfuric acid solution is 1:10.

[0079] Wherein, the preparation method of the sodium polyacrylate modified shell powder comprises the following steps:

[0080] The shell powder, sodium acrylate and initiator are mixed in water, and a polymerization reaction is carried out at 80° C. for 1 hour to obtain the sodium polyacrylate modified shell powder; wherein the mass ratio of the sodium acrylate to the initiator is 1:0.020, the mass ratio of the sodium acrylate to the shell powder is 1:6, and the initiator is potassium persulfate.

[0081] The method for preparing the pigment with a wire drawing effect comprises the following steps:

[0082] S1, stirring and mixing water, sodium polyacrylate modified shell powder, pearl powder, Sanzan glue, defoaming agent and preservative at a speed of 7000 r / min for 20 min to obtain a first mixture;

[0083] S2. Adding sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion and pH regulator to the first mixture, stirring at a rotation speed of 3000 r / min for 10 min to obtain the pigment with drawing effect.

[0084] Example 4

[0085] The difference between Example 4 and Example 1 is that no sodium chloride solution is added to the sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion.

[0086] Example 5

[0087] The difference between Example 5 and Example 1 is that the molar concentration of the sodium chloride solution in the sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion is 25 mmol / L.

[0088] Example 6

[0089] The difference between Example 6 and Example 1 is that the molar concentration of the sodium chloride solution in the sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion is 105 mmol / L.

[0090] Example 7

[0091] The difference between Example 7 and Example 1 is that in the method for preparing the pigment, all components are directly mixed, and the stirring speed and time are the same as those in Example 1.

[0092] Comparative Example 1

[0093] The difference between Comparative Example 1 and Example 1 is that: Comparative Example 1 does not add the sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion, but directly adds an equal amount of polyethylene oxide powder in the emulsion.

[0094] Comparative Example 2

[0095] The difference between Comparative Example 2 and Example 1 is that the mass concentration of polyethylene oxide in the emulsion is 28 wt %, and the mass concentration of sodium polyacrylate is 1.7 wt %.

[0096] Comparative Example 3

[0097] The difference between Comparative Example 3 and Example 1 is that the mass concentration of cellulose nanocrystals in the emulsion is 0.14 wt %.

[0098] Comparative Example 4

[0099] The difference between Comparative Example 4 and Example 1 is that the mass concentration of cellulose nanocrystals in the emulsion is 0.26 wt %.

[0100] Comparative Example 5

[0101] The difference between Comparative Example 5 and Example 1 is that the water-in-water emulsion of sodium polyacrylate / polyethylene oxide / cellulose nanocrystal is replaced by the water-in-water emulsion of sodium polyacrylate / polyethylene oxide, and sodium polyacrylate, polyethylene oxide and water are used as the water phase, and 70% mineral oil, 25% liquid paraffin, and 5% Tween 60 (the above mass percentages are the proportions of the total amount of the oil phase) are used as the oil phase, and the water-in-water emulsion of sodium polyacrylate / polyethylene oxide is obtained after mixing. Among them, the oil phase content is 15%, and the water phase content is 85%. The dispersed oil phase is added to the water phase system, and homogenized by a homogenizer for 2-3 minutes to uniformly disperse the oil phase in the water phase to form an oil-in-water emulsion.

[0102] Comparative Example 6

[0103] The difference between Comparative Example 6 and Example 1 is that the water-in-water emulsion of sodium polyacrylate / polyethylene oxide / cellulose nanocrystal is replaced by an oil-in-water emulsion of sodium polyacrylate / polyethylene oxide, and sodium polyacrylate, polyethylene oxide and water are used as the aqueous phase, and 70% mineral oil, 25% liquid paraffin, and 5% Tween 60 (the above mass percentages are the proportions of the total oil phase) are used as the oil phase. After mixing, a water-in-oil emulsion of sodium polyacrylate / polyethylene oxide is obtained, wherein the oil phase content is 85% and the water phase content is 15%; the dispersed oil phase is added to the aqueous phase system, and homogenized by a homogenizer for 2-3 minutes to uniformly disperse the oil phase in the aqueous phase to form an oil-in-water emulsion.

[0104] Comparative Example 7

[0105] The difference between Comparative Example 7 and Example 1 is that the pigment of Comparative Example 7 does not contain sodium polyacrylate modified shell powder.

[0106] Comparative Example 8

[0107] The difference between Comparative Example 8 and Example 1 is that the shell powder in Comparative Example 8 is not modified by sodium polyacrylate.

[0108] Comparative Example 9

[0109] The difference between Comparative Example 9 and Example 1 is that: Comparative Example 9 does not add trisammonia glue.

[0110] Comparative Example 10

[0111] The difference between Comparative Example 10 and Example 1 is that in Comparative Example 10, triglyceride gum is replaced by guar gum.

[0112] Performance Testing

[0113] 1. Storage stability test of pigments

[0114] The pigment samples of Examples 1 to 7 and Comparative Examples 1 to 10 were subjected to the method of GB / T 6753.3-1986. The samples were placed in sealed containers, respectively, and placed at room temperature (35°C) for 12 months, at -15°C for 3 months, and at 55°C for 3 months. Then, the samples were taken out and the sedimentation degree of the pigments was checked. The specific inspection method was as follows: if there was a crust, the crust should be carefully removed, and then, without vibrating or shaking the pigment container, a spatula was placed vertically at the center of the paint surface, the top of the spatula was aligned with the top surface of the paint can, and the spatula was dropped from this position to measure the sedimentation degree. If the pigment has settled and formed a hard lump at the bottom of the container, the suspended part of the upper liquid was poured into another clean container and stored for later use. Use a spatula to stir the pigment to disperse it, add a small amount of the poured out reserve liquid to remix and disperse it, stir evenly, then gradually add the poured out reserve liquid to stir and mix until the pigment is remixed and dispersed to form a uniform paint suitable for use, or it is determined that the above operation cannot remix and disperse the pigment blocks into a uniform paint. The specific evaluation criteria are shown in Table 1.

[0115] Table 1 Determination criteria for sample sedimentation rating

[0116]

[0117] Table 2 Sedimentation rating of each group of samples under different conditions

[0118]

[0119]

[0120] As can be seen from Table 2, the pigment of Example 1 can still maintain good stability after being placed at a low temperature of -18°C and a high temperature of 55°C for 3 months and at room temperature for 12 months. Compared with the original state of the paint, there is no change, indicating that it has good storage stability.

[0121] In Example 4, no sodium chloride solution is added to the emulsion, and its room temperature stability, low temperature stability and high temperature stability are significantly reduced. This is because sodium chloride promotes the formation of gel by cellulose nanocrystals to improve the interfacial adsorption of the emulsion, thereby improving the storage stability. The stability of Examples 5 to 6 is reduced. This is because if the molar concentration of the sodium chloride solution is lower than 30mM, the polyacrylate and polyethylene oxide will produce phase separation, that is, it is difficult to form a stable gel structure; if the molar concentration of the salt solution is higher than 100mM, the cellulose nanocrystal particles will quickly aggregate, thereby affecting the interfacial adsorption of the particles and causing the emulsion droplets to aggregate. Therefore, when the molar concentration of the salt solution is within the range of 30 to 100mmol / L, the water-in-water emulsion can obtain a relatively stable gel structure, thereby improving the storage stability of the pigment.

[0122] In Example 7, all components are directly mixed, which affects the high temperature stability and low temperature stability. This is because the sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion is added last, which can avoid phase separation of the emulsion and better wrap the pearlescent powder uniformly dispersed in the water.

[0123] Comparative Example 1 is to add only polyethylene oxide powder to the pigment, and its storage stability is greatly reduced. This is because the molecular chain of polyethylene oxide contains a large number of ether bonds (COC), which are easily attacked by oxygen and degraded. Under high temperature storage conditions, the oxidative degradation of PEO will be accelerated, resulting in a decrease in pigment performance, and PEO will also hydrolyze and become ineffective after 6 months at room temperature.

[0124] The mass concentrations of polyethylene oxide and sodium polyacrylate in the emulsion of Comparative Example 2 alternate with those in Example 1, and the content of polyethylene oxide is higher than that of sodium polyacrylate. However, the stability of the pigment is also significantly reduced, indicating that the increase in the amount of polyethylene oxide added will cause the droplets of the emulsion to aggregate, thereby causing serious phase separation of the emulsion, resulting in obvious sedimentation in the pigment after long-term storage.

[0125] In comparative examples 3 to 4, the amount of cellulose nanocrystals added is too much and too little, respectively. If the amount of cellulose nanocrystal dispersion added is less than 0.15wt%, because salt solution is added, positive ions still exist in the system, but the surface of cellulose nanocrystals has a high surface negative charge, so the two will combine, resulting in agglomeration of emulsion droplets, and the stability of the emulsion will be significantly reduced. Within the above range, the emulsion will not phase separate and can maintain good stability. If the amount of cellulose nanocrystal dispersion added is higher than 0.25wt%, obvious cellulose nanocrystal aggregates will appear in the emulsion and the stability of the emulsion will also be reduced.

[0126] Comparative Examples 5 and 6 replace the water-in-water emulsion with an oil-in-water emulsion and an oil-in-water emulsion, respectively, and their stability is lower than that of Example 1, indicating that the water-in-water emulsion has higher stability than the common oil-in-water emulsion and the oil-in-water emulsion, and is not easy to phase separate or demulsify. Moreover, its emulsion system can also protect polyethylene oxide from the influence of high temperature, thereby improving the high temperature resistance and storage period of the pigment. In addition, its emulsion system can also be used as a carrier of the pigment particles in the pearlescent powder to improve its dispersibility in water.

[0127] The pigment of Comparative Example 7 does not contain sodium polyacrylate-modified shell powder, and its storage stability is significantly reduced, because as a stabilizer and dispersant of the system, it can significantly improve the dispersibility of solid particles such as pearlescent powder and polyethylene oxide in water, so that the pigment can still maintain good suspension after long-term storage; while the pigment of Comparative Example 8 only contains shell powder, which is not modified with sodium polyacrylate, so the shell powder is not hydrophilic and is difficult to disperse evenly in water, and the sedimentation degree of the system will be aggravated after long-term storage.

[0128] In Comparative Example 9, no tri-zan gum is added, and the sedimentation degree of the pigment is improved, indicating that tri-zan gum, as a suspending agent, can prevent the sedimentation and aggregation of pigment particles, ensure that the pigment remains stable during storage and use, and tri-zan gum has good thickening, emulsification, weak gel, synergy and other properties under high temperature, high pressure, high salt and high oil conditions. In Comparative Example 10, tri-zan gum is replaced with guar gum. Although guar gum also has the effect of a suspending agent, its high temperature and low temperature resistance performance is obviously not as good as tri-zan gum, indicating that tri-zan gum can strengthen the structure of sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion and improve its stability.

[0129] 2. Mechanical properties test of wire drawing

[0130] Since there is no special test method for the wire drawing strength of pigments, the method of GB / T16777-2008 "Test for tensile strength and elongation at break of waterproof coatings" was used for testing. The pigment samples of Examples 1 to 7 and Comparative Examples 1 to 10 were subjected to wire drawing treatment respectively, and the thickness of the drawn wires was controlled to be (1.5±0.2) mm after solidification, and then the tensile strength and elongation at break of the solidified wire drawing film layer were measured. See Table 3 for details.

[0131] Table 3 Mechanical properties of wire drawing of each group of pigments

[0132] Project / Group Tensile strength MPa Elongation at break / % Example 1 1.20 156.5 Example 2 1.12 150.9 Example 3 1.14 152.4 Example 4 0.89 131.5 Example 5 0.97 142.5 Example 6 1.02 145.0 Example 7 0.99 144.9 Comparative Example 1 0.77 120.1 Comparative Example 2 0.79 125.5 Comparative Example 3 0.76 121.2 Comparative Example 4 0.80 126.5 Comparative Example 5 1.02 146.7 Comparative Example 6 1.04 148.1 Comparative Example 7 0.69 116.0 Comparative Example 8 0.82 128.1 Comparative Example 9 0.89 131.8 Comparative Example 10 0.95 144.3

[0133] like Figures 1-2 It can be seen that the pigment of Example 1 has a wire drawing function, and its wire drawing length is 25 to 35 cm.

[0134] Although the data in Table 3 were tested when the amount of pigment used was relatively large, they are still used as a standard for judging the mechanical properties of the pigments in the examples and comparative examples. The corresponding trends and conclusions can be obtained by comparing the data of each group, as follows:

[0135] It can be seen from Table 3 that the wire drawing of the pigments of Examples 1 to 3 has good strength and toughness after drying, which can make the painting have a wire drawing texture, and the wire drawing is not easy to fall off.

[0136] In Example 4, no sodium chloride solution was added to the emulsion, resulting in demulsification in the water-in-water emulsion, and then the PEO therein was unevenly dispersed, affecting the mechanical strength of the wire drawing. The wire drawing strengths of Examples 5 to 7 were all reduced, so the more stable the water-in-water emulsion structure, the better the strength and toughness of the wire drawing.

[0137] In comparative example 1, only polyethylene oxide powder is added to the pigment. It is difficult for the PEO powder to be evenly distributed in the pigment, and particles are mixed in the wire drawing, resulting in a decrease in strength and toughness.

[0138] The same conclusion as the above storage stability, the parameters in Comparative Examples 2 to 4 all have a significant impact on the stability of the water-in-water emulsion, thereby affecting the stability of the pigment, which will also affect the mechanical properties of the wire drawing. The types of emulsions in Comparative Examples 5 to 6 are similar. The water-in-water emulsion used in Example 1 is more stable than other emulsions, and its wire drawing strength is also better.

[0139] In comparative example 7, no sodium polyacrylate modified shell powder is added to the pigment, and the strength and toughness of the wire drawing are significantly reduced, indicating that shell powder is an important parameter affecting the strength of the wire drawing. In comparative example 8, shell powder that has not been modified with sodium acrylate is added, and its hydrophilicity is poor. The shell powder cannot be evenly dispersed in water, resulting in uneven wire drawing, and the strength and toughness are also reduced.

[0140] Similar to the conclusion of the above storage stability, the parameters of Comparative Examples 9 to 10 have a significant impact on the suspension stability of the system. Since the dispersion of the solid particles is not good, the mechanical properties of the wire drawing will also be affected.

[0141] In summary, the pigment of the present invention has a wire drawing effect, and the wire drawing length can reach 25-35 cm. Moreover, the pigment can be stably placed at a low temperature of -18°C and a high temperature of 55°C for 3 months, and can be placed at room temperature for 12 months without hydrolysis and failure, and has good storage stability.

[0142] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A pigment with a brushed effect, characterized in that: The invention comprises the following components by weight: 15-20 parts of sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion, 5-10 parts of sodium polyacrylate modified shell powder, 1-5 parts of tri-zan gum, 5-10 parts of pearl powder, 0.2-0.5 parts of defoaming agent, 0.1-0.3 parts of preservative, 0.3-1 parts of pH regulator and 60-80 parts of water; wherein the mass concentration of polyethylene oxide in the emulsion is 1.5-1.8wt%, the mass concentration of sodium polyacrylate is 25-30wt%, and the mass concentration of cellulose nanocrystal is 0.15-0.25wt%; The preparation method of the sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion comprises the following steps: (1) mixing a polyethylene oxide dispersion and a sodium polyacrylate dispersion under stirring to obtain a transparent and clear water-in-water emulsion of polyethylene oxide and sodium polyacrylate; (2) adding a cellulose nanocrystal dispersion to the polyethylene oxide and sodium polyacrylate water-in-water emulsion, stirring evenly, and then adding a salt solution, stirring evenly, to obtain a sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion, wherein the salt solution is a sodium chloride solution with a molar concentration of 30-100 mmol / L; The preparation method of the sodium polyacrylate modified shell powder comprises the following steps: mixing the shell powder, sodium acrylate and an initiator in water, and performing a polymerization reaction to obtain the sodium polyacrylate modified shell powder; the mass ratio of the sodium acrylate to the initiator is 1:0.015-0.020, and the mass ratio of the sodium acrylate to the shell powder is 1:(4-6); The method for preparing the cellulose nanocrystal dispersion comprises the following steps: The microcrystalline cellulose powder is added to a sulfuric acid solution for hydrolysis reaction, and then a large amount of water is added to terminate the reaction, and then centrifugation and water washing are performed until the pH value of the system is 6-7, and the turbid supernatant is taken to obtain the cellulose nanocrystal dispersion.

2. The pigment with a brushed effect according to claim 1, characterized in that: The polymerization reaction temperature is 70-80° C. and the reaction time is 1-3 hours.

3. The pigment with a brushed effect according to claim 1, characterized in that: Each component in the pigment is selected from at least one of the following (I) to (III): (I) the pH adjusting agent is aminomethyl propanol; (II) the defoaming agent is ethylene glycol; (III) The preservative is isothiazolinone.

4. The method for preparing a pigment having a wire drawing effect according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, stirring and mixing water, sodium polyacrylate modified shell powder, pearl powder, Sanzan glue, defoaming agent and preservative to obtain a first mixture; S2, adding sodium polyacrylate / polyethylene oxide / cellulose nanocrystal water-in-water emulsion and pH regulator to the first mixture, stirring evenly, to obtain the pigment with drawing effect; Wherein, in the step S1, the stirring speed is 6000-7000 r / min, and the time is 20-30 min; in the step S2, the stirring speed is 2000-3000 r / min, and the time is 10-20 min.

5. The pigment with a brushed effect according to any one of claims 1 to 3 is used for preparing children's products.

Citation Information

Patent Citations

  • Drawing pigment and its production method

    CN1322071C

  • Drawing pigment and its production method

    CN1676552A